Histochemical Studies of Teat in Kosali Cow - K Deshmukh, Shivesh; P Ingole, Sanjay; Chaurasia, Durga; K Dewangan, Bhupendra; Rajput, Abhishek (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was conducted on mammary glands of 36 lactating and non-lactating Kosali cows divided into early, mid and late stages, respectively. Kosali, the first breed of cattle from Chhattisgarh, was registered as 36th breed of nation. Kosali cattle are smaller in size and are well adapted to the existing agro-climatic conditions of the region. Collagen fibers in teat were most abundant followed by reticular and elastic fiber. Their density was apparently increased with advancement of lactation from early to late stage. These fibers were more compact and denser in non-lactating/non-pregnant Kosali cows. Epithelium of teat cistern, rosette of Furstenberg and teat canal were positive for PAS and AB-PAS substance in variable range in lactating and non-lactating stage and the reaction was weak in non-lactating group.